What causes housing bubbles? A theoretical and empirical inquiry - Heike Joebges; Sebastian Dullien; Alejandro Márquez-Velázquez (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
The paper investigates in how far lax monetary policy (defined as deviations from prescriptive monetary policy rules or past trends) and/or financial innovation can be seen as a cause for housing price bubbles in industrialized countries. From a theoretical perspective, it is found that there are hardly any clearly formulated economic models which assign a role to lax monetary policy in bubble formation, while there are a number of models which assign a role to financial innovation or liberalization. In the empirical part, the paper first presents cross-country-time-series SUR regressions for a sample of 16 industrialized countries. According to the results, there is no robust, significant role for the relevance of loose monetary policy, measured by deviations from the Taylor rule. Instead, deviations from the past trend of the real policy rate affect housing prices, but the size of the effect depends on the regulation and development of the financial sector. In a third step, three case studies of the United States, Austria and the United Kingdom are presented, representing countries which have experienced a) lax monetary policy and a bubble b) lax monetary policy without a bubble and c) no deviation from the Taylor rule and a bubble. The case studies hint that specific changes in regulations played a role for the emergence or absence of bubbles, yet these regulations might not be appropriately covered by standard quantitative indicators for financial market (de-)regulation. – – Die Arbeit untersucht, inwieweit eine lockere Geldpolitik (definiert als Abweichung von gängigen geldpolitischen Regeln oder früheren Trends) und/oder Finanzinnovationen als Ursache von Hauspreisblasen betrachtet werden können. Dabei wird zunächst festgestellt, dass es kaum theoretische Modelle gibt, die einer zu lockeren Geldpolitik eine plausible Rolle in der Entstehung von Hauspreisblasen zuweisen. Finanzinnovationen oder Deregulierung können dagegen nach mehreren Modellen Auslöser von Preisblasen sein. Im empirischen Teil wird zunächst eine SUR-Regression für ein Sample von 16 Industrieländern vorgestellt. Dabei kann kein robuster signifikanter Einfluss der Abweichung des kurzfristigen Zinses von den Empfehlungen der Taylor-Regel auf die Entstehung von Hauspreisblasen gezeigt werden. Allerdings deuten die Ergebnisse darauf hin, dass eine Abweichung des kurzfristigen Realzinses von früheren Trends einen Einfluss auf Hauspreise hat, aber die Stärke dieses Einflusses von der Struktur und Regulierung des nationalen Finanzsystems abhängt. In einem dritten Schritt werden drei Fallstudien zur Hauspreisentwicklung in den USA, Österreich und Großbritannien präsentiert, da diese Länder Fälle repräsentieren, in denen es a) eine lockere Gelpolitik und eine Hauspreisblase, b) eine lockere Geldpolitik ohne Hauspreisblase und c) keine lockere Geldpolitik, aber eine Hauspreisblase gegeben hat. Die Fallstudien deuten darauf hin, dass länderspezifische Regulierungen eine wichtige Rolle bei der Entstehung von Hauspreisblasen gespielt haben, diese Regulierungen aber oft nicht vollständig in gängigen quantitativen Indikatoren zur Finanzmarktentwicklung abgebildet sind.
urn:nbn:de:101:1-201602195116
Keywords: 330